Plagiat w dobie sztucznej inteligencji - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
This essay is devoted to theoretical reflections on the practice of using text-generating artificial intelligence programs for plagiarism. The author puts forward the thesis that network tools and advanced AI programs are not the “culprits”: the real perpetrator of plagiarism always turns out to be the person who used them for this purpose.